ANALISIS OPTIMALISASI PEMUNGUTAN PAJAK HIBURAN DALAM MENINGKATKAN PENERIMAAN PAJAK DAERAH PADA SUKU BADAN PENDAPATAN DAERAH KOTA ADMINISTRASI JAKARTA PUSAT - Simamora, Erwin Romy Natanael; Wahyudin, Dian (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Entertainment tax is included in the type of tax that is part of regional income. Entertainment tax is taken based on ownership of entertainment venues in administrative areas that have a tax management body. The implementation of entertainment tax collection is carried out in order to increase Regional Tax revenues. This research on the effectiveness of entertainment tax collection aims to analyze Entertainment Tax collection along with obstacles and efforts to improve regional development. In this research the author used a qualitative approach and descriptive method. The results of this research show that the level of effectiveness of entertainment tax collection is seen from the target data and the realization exceeds the target with quite effective indicators. There is also an obstacle, namely the lack of awareness of tax objects in inputting original transaction data so that there is a gap in tax reporting. Even though there are these obstacles, tax collection officers take a communicative approach to resolve these obstacles so that they are completed correctly and efficiently.